Automatic postprocessing and reporting tools for functional neuroimaging - Demirel, Engin. (Thesis (M.S.)-Bogazici University. Institute of Biomedical Engineering, 2010., 2010)
For advanced magnetic resonance imaging (MRI) applications, reporting and postprocessing tools have been designed. The software tools developed consist of DICOM structured report (DICOM SR) preparation, functional image overlay onto anatomical standard atlases, lateralization calculations, maximum Z value and location analysis and mean Z value analysis for cortical and subcortical brain regions. Radiologists can view the functional image overlayed onto the anatomical ones, visualize the activated regions and edit DICOM SR accordingly with the image references. Lateralization calculation is automatically done and displayed on the user interface. Maximum Z value is found and shown on standard anatomical atlas in axial, sagital and coronal planes with the waveform of the maxima through the timepoints of the data analyzed. The software nally provides the user with DICOM SR and rich text format (RTF) output including edited DICOM SR text elds, referenced images, lateralization or maximum Z value calculations.|Keywords: DICOM SR, Lateralization, Z score, Reporting, Neuroimaging.
Keywords: Imaging systems in medicine.; Magnetic resonance imaging.; Cerebral dominance.; Brain -- Magnetic resonance imaging.